Winter of the world - Follett, Ken. (London : Pan Books, 2013)
Carla von Ulrich, born of German and English parents, finds her life engulfed by the Nazi tide until she commits a deed of great courage and heartbreak. American brothers Woody and Chuck Dewar, each with a secret, take separate paths to momentous events, one in Washington, the other in the bloody jungles of the Pacific. English student Lloyd Williams discovers in the crucible of the Spanish Civil War that he must fight Communism just as hard as Fascism. Daisy Peshkov, a driven American social climber, cares only for popularity and the fast set, until the war transforms her life, not just once but twice, while her cousin Volodya carves out a position in Soviet intelligence that will affect not only this war - but the war to come. These characters and many others find their lives inextricably entangled as their experiences illuminate the cataclysms that marked the century. From the drawing rooms of the rich to the blood and smoke of battle, their lives intertwine, propelling the reader into dramas of ever-increasing complexity.
Keywords: World War, 1939-1945 -- Social aspects -- Fiction; Twentieth century -- Fiction; Spain -- History -- Civil War, 1936-1939 -- Fiction